Review of Health Prognostics and Condition Monitoring of Electronic Components - Bhargava C.; Sharma P.K.; Senthilkumar M.; Padmanaban S.; Ramachandaramurthy V.K.; Leonowicz Z.; Blaabjerg F.; Mitolo M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Failure (mechanical); Green manufacturing; Network components; Reliability analysis; Electronic component; Failure mechanism; Fault diagnosis technique; Health prognostics; Intelligent tools; Reliable electronics; Remaining useful life predictions; Residual lifetime; Condition monitoring